Pharmacogenetics of clinical response to risperidone. (January 2013) - LLerena, Adrián; Berecz, Roland; Peñas-LLedó, Eva; Süveges, Ágnes; Fariñas, Humberto
Despite risperidone's proven safety and efficacy, existing pharmacogenetic knowledge could be applied to improve its clinical use. The present work aims to summarize the information about genetic polymorphisms affecting risperidone adverse reactions and efficacy during routine clinical practice. The most relevant genes involved in the metabolism of the drug (i.e., CYP2D6, CYP3A and ABCB1 ) appear to have the greatest potential to predict differences in plasma concentrations of the drug and its interactions, but also relate to side effects, such as neuroleptic syndrome, weight gain or polydipsia. Other genes that have been found in association at least twice with any adverse reactions including metabolic changes, extrapyramidal symptoms or prolactine increase are: 5HT2A ; 5HT2C ; 5HT6 ; DRD2 ; DRD3 ; and BDNF . Some of these genes ( 5HTR2A, DRD2 and DRD3 ), along with 5-HTTLPR and COMT, have also been reported to be related with negative clinical outcomes. However, there is not yet enough evidence to support their routine screening during clinical practice.